Measuring effective teaching: Student perceptions of their modern languages lessons in England. (April 2021) - Molway, Laura
Abstract: Evaluating the quality of classroom teaching is a complex task. Alongside observation tools and value-added student attainment measures, there is growing international interest in the potential of student perception surveys (SPS), which gather data about teaching practices from whole classes of first-hand observers. This paper reports on the refinement and trial of an existing SPS (available from the Colorado Education Initiative) to make it specific to the teaching of modern languages. Using both student (n = 1370) and teacher (n = 41) surveys, and follow-up interviews with Heads of Department (n = 6), the paper investigates students' classroom experiences of French lessons across fourteen secondary schools. The SPS_ML was was found to have high levels of internal reliability and provided data that correlated with a range of other known measures of effective teaching. Three distinct, languages-specific factors emerged from a factor analysis, which is interpreted as strong support for a subject-specific approach to developing measures of effective teaching. The three development areas suggested by the data relate to 1) the teachers' responsiveness to the needs and interests of their students; 2) the motivation and engagement of students in language lessons; and 3) the extent to which students are encouraged to adopt strategic approaches to language tasks. Highlights: A student perception survey tool for modern languages classrooms was tested. The survey was reliable and correlated with other measures of effective teaching. Students gave low scores for student behaviour and engagement in language lessons. Experiences of authentic resources and learning strategies were rarely reported. Teachers valued the subject-specific survey feedback for professional learning.